P442 Endoscopic resection of visible precancerous lesions in patients with colonic Inflammatory Bowel Disease. (30th January 2023) - Busacca, A; De Sire, R; Capogreco, A; Dal Buono, A; Gabbiadini, R; Loy, L; Finati, E; Spadaccini, M; Maselli, R; Hassan, C; Repici, A; Armuzzi, A
Abstract: Background: IBD patients have an increased risk of reporting a colorectal cancer. According to SCENIC, endoscopic resection (ER) should be preferred to biopsies for visible precancerous lesions in absence of stigmata of invasive cancer or submucosal fibrosis. However, the evidence is still lacking on specific outcomes of ER for the management of dysplastic lesions in IBD. Aim of this study was to evaluate the effectiveness and safety of ER of visible precancerous lesions in IBD patients. Methods: In this retrospective study, we included consecutive IBD patients referred to an Endoscopy Unit (2016-2022) to undergo a ER, including endoscopic mucosal resection (EMR), endoscopic submucosal dissection (ESD) and hybrid EMR-ESD (hESD), of visible precancerous lesions. The primary outcome was the assessment of rates of en bloc resection, R0 resection and adverse events (AEs). The secondary outcome was the rate of post-ER surgery and surgery for refractory IBD. En bloc resection was defined as excision of the targeted lesion in a single specimen. R0 resection was defined as resection with lateral and deep margins free of dysplasia/neoplasia on histopathology. Among AEs, we considered bleeding and perforation. Results: A total of 67 visible lesions (64.18% non-polypoid, 53.73% left-side colon, median size 25 mm± 20 mm, 65.67% neoplastic pit-pattern) in 67 patients with colonic IBD (56.72% male, median age 58 yrs± 15 yrs, 68.66% ulcerative colitis, median disease duration 160 months± 98 months, 58.21% active disease) were included. ESD, hESD, and EMR was performed in 20.9%, 6%, and 73.1% of cases. The final histopathological diagnoses after ER were inflammatory polyp in 32.84%, SSL in 8.96%, LGD in 40.30%, HGD in 13.42%, adenocarcinoma in 2.99%, and squamous cell carcinoma in 1.49% of cases. Excluding inflammatory polyps, en bloc resection was achieved in 14/14(100%), 3/4(75%), and 15/27(55%) lesions in case of ESD, hESD, and EMR (ESD+hESD vs EMR p<0.05). R0 resection was achieved in 12/14(86%), 3/4(75%), and 15/27(55%) lesions in case of ESD, hESD, and EMR (ESD+hESD vs EMR p=0.05). AEs occurred in 21% (2 bleedings and 1 perforation), 0%, and 3% (1 perforation) of patients treated by ESD, hESD and EMR (ESD+hESD vs EMR p=N.S.). Post-ER surgery rate was 21%, 25%, and 3% for patients treated by ESD, hESD, and EMR. Surgery for refractory IBD rate was 7%, 0%, and 18% for patients treated by ESD, hESD, and EMR. Conclusion: Our findings showed that ER (including ESD, hESD, and EMR) of visible precancerous lesions performed in a tertiary center might be considered feasible, safe and effective in IBD patients, despite the presence of submucosal fibrosis. These data should be confirmed in a wider IBD population referring from different specialized Endoscopy Units.